Few-layer antimonene decorated microfiber: ultra-short pulse generation and all-optical thresholding with enhanced long term stability. (6th September 2017) - Song, Yufeng; Liang, Zhiming; Jiang, Xiantao; Chen, Yunxiang; Li, Zhongjun; Lu, Lu; Ge, Yanqi; Wang, Ke; Zheng, Jilin; Lu, Shunbin; Ji, Jianhua; Zhang, Han
Abstract: Antimonene, a new type of mono/few-layer two-dimensional (2D) mono-elemental material purely consisting of antimony similar as graphene and phosphorene, has been theoretically predicted with excellent optical response and enhanced stability. Herein, we experimentally investigated the broadband nonlinear optical response of highly stable few-layer antimonene (FLA) by performing an open-aperture Z-scan laser measurement. Thanks to the direct bandgap and resonant absorption at the telecommunication band, we demonstrated the feasibility of FLA-decorated microfiber not only as an optical saturable absorber for ultrafast photonics operation, but also as a stable all-optical pulse thresholder that can effectively suppress the transmission noise, boost the signal-to-noise ratio (SNR), and reshape the deteriorated input signal. Our findings, as the first prototypic device of absorption of antimonene, might facilitate the development of antimonene-based optical communication technologies towards high stability and practical applications in the future.